Pelatihan Penyusunan Lembar Kerja Peserta Didik (LKPD) Berbasis Science, Technology, Engineering, Mathematic (STEM) dan Karakter Bagi Guru Sekolah Dasar Kecamatan Batang Kapas Kabupaten Pesisir Selatan - Rusdinal Rusdinal; Rifma Rusli; Ranti Meizatri (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The content and implementation of learning must always adapt to changes and development demands that can answer 21st-century skills. On the other hand, the teacher is an important factor in implementing learning that refers to the development of student competencies. The adjustment of the learning content must be in line with the adjustment/increase of the competence of the teacher as the perpetrator of the implementation of the learning itself. The current learning demands should focus on students as the main learning subjects in the classroom. Training on Preparation of Student Worksheets Based on Science Technology Engineering and Mathematics (STEM) and character was given to 32 elementary school teachers in Batang Kapas District, Pesisir Selatan Regency. The implementation of this training is divided into two segments: (1) delivery of material with an accumulation of 16 hours of lessons and (2) guided assignments with an accumulation of 16 hours of lessons. The effectiveness of the training is determined by comparing the results of the pre-test and post-test of the trainees. The results of the analysis can be concluded that there is an increase in teacher understanding of 27.5% in aspects: 1) 2013 curriculum and integrated thematic learning, (2) STEM approach in learning (3) HOTS-based learning, (4) integration of character values in learning, and (5) the basics of preparing student worksheets.